Dreams, depths, and dual meanings: A semiotic analysis of symbols in Inception (2010) film - Saputra, Andrey; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This study discusses the symbolism in the film “Inception” by Christopher Nolan (2010) using Roland Barthes semiotic approach. Films are understood not only as visual entertainment, but also as cultural texts that contain social, ideological and philosophical messages. Through qualitative analysis, data is collected from movie scenes, dialogues and visual elements, and then interpreted based on three layers of meaning: denotation, connotation and myth. An analysis of the seven main scenes shows that “Inception” features several major themes: (1) trauma and uncertainty that continue to haunt humans, depicted through Cobb's characters and rotating totem symbols; (2) reality as fragile and reconstructable, seen from the folds of Paris and the rotating corridors of hotels; (3) Science and technology as a form of control over the unconscious, shown by Joseph; (4) the human subconscious as a battleground of ideas and resistance, visualized through snow; and (5) family and personal relationships as an important part of identity formation, for example through Fischer's conflict with his father. These findings confirm that “Inception” presents a grand narrative about human life, full of ambiguity, trauma and the search for meaning. Thus, the film can be read as a representation of the modern human condition, living between reality and illusion, technological control and inner freedom, as well as past demands and future expectations.